2016
DOI: 10.15517/rbt.v64i4.21219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de AE y PAE para identificar trazos generalizados, a partir de las serpientes del estado de Hidalgo, México

Abstract: One of the most important concepts in Panbiogeography is the generalized track, which represents an ancestral biota fragmented by geological events that can be recovered through several methods, including Parsimony analysis of endemicity (PAE) and endemicity analysis (EA). PAE has been frequently used to identify generalized tracks, while EA is primarily designed to find areas of endemicity, but has been recently proposed for identifying generalized tracks as well. In this study we evaluated these methods to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
1
0
2
Order By: Relevance
“…Ferrari, Barao, and Simoes () compared the performance of MartiTracks with PAE and track compatibility, finding that MartiTracks does not provide reliable results because it lacks clear congruence criteria—the parameter definition is subjective and has unclear analytical procedures. Montiel‐Canales, Goyenechea, Fernández‐Badillo, and Castillo‐Cerón () compared PAE and AE and concluded that these two methods can be complementary. Escalante et al.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrari, Barao, and Simoes () compared the performance of MartiTracks with PAE and track compatibility, finding that MartiTracks does not provide reliable results because it lacks clear congruence criteria—the parameter definition is subjective and has unclear analytical procedures. Montiel‐Canales, Goyenechea, Fernández‐Badillo, and Castillo‐Cerón () compared PAE and AE and concluded that these two methods can be complementary. Escalante et al.…”
Section: Introductionmentioning
confidence: 99%
“…Así, al analizar cladogramas construidos a partir de matrices de presencia/ausencia de especies (trazos individuales), las sinapomorfías que agrupan las áreas son indicativas de las distribuciones de los taxones. Teniendo en consideración que un trazo generalizado representa la congruencia geográfica de al menos dos taxones (equivalentes a las sinapomorfías), este método resulta adecuado para reconocer trazos generalizados cuando se obtienen al menos dos sinapomorfías (Morrone, 2015;Montiel-Canales et al, 2016). Además, el PAE permite observar gráficamente las relaciones entre las áreas estudiadas (Morrone, 2014).…”
Section: Materiales Y Métodosunclassified
“…Entre las especies que conforman este patrón destacan: Hymenophyllum tegularis, Holodictyum ghiesbreghtii, Elaphoglossum obscurum y Phanerophlebia nobilis, especies consideradas dentro de las más ricas en el BMM de Hidalgo de acuerdo conHernández-Álvarez et al (2019). Este trazo generalizado, que une a la PV y SMO, es congruente con los resultados obtenidos porMontiel-Canales et al (2016) para la distribución de las serpientes en Hidalgo y porMorrone & Gutiérrez (…”
unclassified